(untitled) (The International Journal for Scientific Research, 2025)
The research aimed to identify the role of the cybercrime combating system in the Kingdom of Saudi Arabia, the level of regulation of digital media ethics, and to reveal the relationship between the role of the cybercrime combating system and the regulation of digital media ethics in the Kingdom of Saudi Arabia. The research community consisted of media professionals and activists working on digital media platforms in the Kingdom of Saudi Arabia. The research sample included (94). The researcher used the analytical approach as a study method and used it as a study tool. The research reached a number of results, the most important of which were: The general average for the first axis: the cybercrime combating system came with a (high) response degree, and the general average for the second axis: regulating digital media ethics came with a (medium) response degree, and there is a positive correlation with statistical significance between the role of the cybercrime combating system and regulating digital media ethics in the Kingdom of Saudi Arabia. The research recommended many recommendations, the most important of which were: establishing strict legislation and laws to combat cybercrime, and clearly declaring digital media ethics.